Pentingnya Nilai Profesional dari Perspektif Mahasiswa Keperawatan di Jember - Ika Adelia Susanti; Prestasianita Putri; Emi Eliya Astutik (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
The professional value of nurses becomes an important element. Professional value in nursing is recognized as an essential aspect to be considered among nursing students. These values can be modified through educational, clinical, and personal experiences. Educational institutions have an important role in shaping the professional value of nursing students. The study aimed to analyze the importance of professional value from the perspective of nursing students. The research design used a descriptive study with a cross-sectional approach. The research sample was 117 2nd semester nursing students with consecutive sampling techniques. The research instrument used the Nurse Professional Values Scale-Revised (NPVS-R) questionnaire. Data analysis using descriptive analysis. The results showed that the students' professional scores were quite high with a total score of 94.43 ± 14.28 and an average score of 3.63. Based on the perspective of nursing students, the highest domain in professional values was the